2017
DOI: 10.5194/amt-10-3931-2017
|View full text |Cite
|
Sign up to set email alerts
|

CH<sub>4</sub> emission estimates from an active landfill site inferred from a combined approach of CFD modelling and in situ FTIR measurements

Abstract: Abstract. Globally, the waste sector contributes to nearly a fifth of anthropogenic methane emitted to the atmosphere and is the second largest source of methane in the UK. In recent years great improvements to reduce those emissions have been achieved by the installation of methane recovery systems at landfill sites, and subsequently methane emissions reported in national emission inventories have been reduced. Nevertheless, methane emissions of landfills remain uncertain and quantification of emission fluxes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The audit results show the FTIR CO 2 and CH 4 measurements to be comparable to other measurement types (N 2 O and CO were not assessed). Other studies have shown the durability and reliability of the FTIR during field campaigns (Deutscher et al, 2010b;Laubach et al, 2016;Sonderfeld et al, 2017).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The audit results show the FTIR CO 2 and CH 4 measurements to be comparable to other measurement types (N 2 O and CO were not assessed). Other studies have shown the durability and reliability of the FTIR during field campaigns (Deutscher et al, 2010b;Laubach et al, 2016;Sonderfeld et al, 2017).…”
mentioning
confidence: 94%
“…Second, it was to provide a complementary in situ measurement site to that at Baring Head,New Zealand (41.41 S,174.87 E, 85 m a. m. s. l.) (Brailsford et al, 2012) as a first step in a New Zealand carbon monitoring network. Measurements from these two sites have been used in a regional atmospheric inversion method determining CO 2 sinks and sources across New Zealand (Steinkamp et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…rotary UAVs, to develop and refine new methods to use atmospheric measurements to quantify CH 4 and CO 2 emission from a landfill site (Riddick et al, 2016;Sonderfeld et al, 2017;Allen et al, 2017;Riddick et al, 2017). This represents one of the first demonstrations of using UAVs to sample GHG emissions.…”
mentioning
confidence: 99%
“…Sonderfeld et al (2017) The underlying idea is that taking the ratio of the CH 4 and CO 2 fitted in nearby wavelength regions effectively removes spectral artefacts common to both CH 4 and CO 2 (e.g., scattering). The conventional method of using these data is to multiply the ratio by model CO 2 , assuming that CO 2 varies in space and time less than CH 4 .…”
mentioning
confidence: 99%